Mandibular lingual vascular canals (MLVC): evaluation on dental CTs of a case series. - Scaravilli MS; Mariniello M; Sammartino G; Scaravilli, Maria Serena; Mariniello, Mauro; Sammartino, Gilberto (European Journal of Radiology, 2010)
Purpose: The aim of this study was to assess the anatomy of the mandibular lingual foramen (MLF) and its linked canals (mandibular lingual vascular canals - MLVC), describing their frequency, diameter, location, and course. Materials and Methods: One hundred and fourteen computed tomography (CT) images of the mandible (57 male and 57 female; mean age 44.70±12.53; age range 13-75 years, were evaluated. The CT sections were obtained on axial plane by using a bone reconstruction algorithm and then processed with dedicated software (Dentascan), with a standard protocol. Results: 103 patients (90.35%) had at least one lingual vascular canal and 52 (45.61%) had multiple (two or three) canals. The typical locations of MLVC were the midline of the mandible (median lingual canal [MLC]). The mean diameter of the lingual canals in the midline (MLC) was 0.8mm±0. The direction of MLC progresses in an anterior and slightly caudal sense. Conclusions: Dental CT examination easily demonstrates the presence, position, direction and size of the lingual foramen and of the lingual vascular canals of the mandible. Radiologists and oral surgeons should be aware of these canals and their importance, in order to prevent bleeding complications during implants placement and other surgical procedures.